Simple Regression Model Analysis of the Effect of Temperature on Rainfall in Padang City Using Scikit-Learn - Nelvidawati Nelvidawati (Politeknik Negeri Padang, 2024)
Temperature is one of the factors that influences the intensity of rainfall in an area. The higher the temperature in an area, the higher the evaporation so the greater the chance of rain, especially if this occurs at sea. The location of Padang City close to the sea influences the intensity of rainfall that occurs. Research was conducted to model the effect of temperature on rainfall that occurs in Padang City using simple linear regression using the Python programming language. The methodology used to model the relationship between these two variables is the Cross-Industry Standard Process for Data Mining. The simple regression model equation obtained is y = -26.73 x + 1119.98. The evaluation carried out on the model resulted in a relationship that was not close and had a negative correlation. The error rate of the simple linear regression model used in this study is quite large with a mean model error value of 40%, an MAE value of 124.2311, MSE 23489.97 and RMSE 153.2644. A good model has MAE, MSE and RMSE close to zero. Further research is needed to find out a suitable model to describe the relationship between temperature and rainfall that occurs in Padang City.